Projections of Energy Use and Carbon Emissions for Bangkok, Thailand - Phdungsilp, Aumnad (Journal of Reviews on Global Economics, 2017)
Cities around the world have developed innovative plans and strategies to reduce rampant and uncontrolled energy use and CO2 emissions. It is not surprising that many cities have adopted long-term emission reduction goals. However, a detailed analysis of energy use and the resulting carbon emissions are rare in developing countries. This paper presents historical trends of energy demand and energy-related CO2 emissions for Bangkok, Thailand. The CO2 emissions account for the use of fossil fuels only. It also presents the projections of energy use and CO2 emissions from 2010 to 2050. Using a bottom-up energy model and scenario analysis, the paper employs a Long-range Energy Alternative Planning (LEAP) system to simulate four sectors in Bangkok. The results identified by the BAU (business-as-usual) scenario indicate that total energy is expected to reach 54,560 kilotonne of oil equivalent (ktoe) with 191 million tonne CO2 (Mt-CO2) by 2050. Under the alternative scenario, if all policy interventions are implemented simultaneously, the potential for energy-savings and reduced CO2 emissions in 2050 are estimated to be 32,120 ktoe and 106.19 Mt-CO2. Other international cities may wish to apply the strategies and analytical approaches presented in this paper for developing appropriate policies and measures in their own jurisdictions.